2003
DOI: 10.1002/jsfa.1360
|View full text |Cite
|
Sign up to set email alerts
|

Temperature–time relationships for thermal inactivation of pectinesterases in orange juice

Abstract: The first-order kinetic model of a two-component system was applied to calculate the necessary parameters using the commercial Mathcad program package during the experimental thermal pasteurisation of Valencia orange juice. Thermostable and thermolabile pectinesterases, accounting for 6.6 and 93.4% of the total enzyme population in the juice respectively, showed a 5.63°C Z s value and a 9.54°C Z l value respectively from the thermal destruction curves at temperatures ranging from 75 to 90°C. The calculated Z s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 7 publications
0
23
0
1
Order By: Relevance
“…Approximately 4-5 % of the PME remained after the 90 °C treatment. Several authors (Veersteg et al, 1980;Wicker and Temelli, 1988;Snir et al, 1996;Cameron et al, 1996;Tajchakavit and Ramaswami, 1997;Cameron et al, 1998;Lee et al, 2003;Do Amaral et al, 2005) have also observed a residual activity after thermal treatment, considered the stable fraction, between 4-8.3% in Navel and Valencia var. oranges reflecting the thermotolerance of the orange PME.…”
Section: Effect Of Treatment On Pme Activity In the Orange Juice-milkmentioning
confidence: 99%
See 4 more Smart Citations
“…Approximately 4-5 % of the PME remained after the 90 °C treatment. Several authors (Veersteg et al, 1980;Wicker and Temelli, 1988;Snir et al, 1996;Cameron et al, 1996;Tajchakavit and Ramaswami, 1997;Cameron et al, 1998;Lee et al, 2003;Do Amaral et al, 2005) have also observed a residual activity after thermal treatment, considered the stable fraction, between 4-8.3% in Navel and Valencia var. oranges reflecting the thermotolerance of the orange PME.…”
Section: Effect Of Treatment On Pme Activity In the Orange Juice-milkmentioning
confidence: 99%
“…However, in the case of different enzymes thermal inactivation curves have been observed to behave differently due to the presence of different fractions exhibiting different stabilities (Hou et al, 1997;Lee et al, 2003; INTRODUCTION 50 Tajchakavit and Ramaswamy, 1997; Van den Broeck et al, 1999 a; Wicker and Temelli, 1988;Cameron et al, 1998;Han et al, 2000; Versteeg et al, 1980). Nevertheless, in many cases only part of the curve (activity related to the most abundant fraction) has been modelled to obtain the previously described parameters.…”
Section: Primary Modelsmentioning
confidence: 99%
See 3 more Smart Citations